1, 3‐Thiazolium‐4‐aminides: Syntheses and Characterization of Fluorescent Mesoionic Compounds. Issue 34 (8th September 2021) - Storm, Alena Therese; Gjikaj, Mimoza; Namyslo, Jan C.; Adams, Jörg; Schmidt, Andreas
Abstract: A series of mesoionic 1, 3‐thiazolium‐4‐aminides was synthesized starting from thioamides and chloroacetonitrile via cyanomethylbenzimidothioates which were cyclized by benzoylchloride. Depending on the reaction conditions 4‐amino‐1, 3‐thiazolium salts and 4‐ N ‐benzamido‐1, 3‐thiazolium salts were obtained (X‐ray structure analysis). Substitution of the amino groups with benzoyl chloride gave a series of the title mesoionic compounds (X‐ray structure analysis) which were examined spectroscopically. Negative solvatochromism was found and temperature‐dependent as well as time‐resolved fluorescence measurements were made. Long lifetimes of the excited states (30–50 ns) were detected. Calculated frontier orbital profiles gain insight into the characteristics of 1, 3‐thiazolium‐4‐aminides as conjugated mesomeric betaines. Abstract : Series of mesoionic 1, 3‐thiazolium‐4‐aminides are prepared, some of which are fluorescent in the solid state. Characteristic for conjugated mesomeric betaines, the formal positive and negative charges are delocalized within the common π‐electron system according to the rules of resonance. X‐ray structure analyses, DFT‐calculations of the frontier orbitals, and fluorescence measurements were carried out.